Effects of chemical disinfectants on surface hardness of heat -cured acrylic resins. In vitro study - Firas Abd Kati (Universidad de Concepción., 2021)
Introduction: Acrylic resins (i.e., heat cured acrylic resins) are the most common materials used to manufacture removable dental prostheses involving maxillofacial prostheses such as obturators. Their mechanical and physical properties must be adequate for their use and durability. It is therefore vital to assess how their properties are affected by different disinfectants. Aims: The purpose of this research was to evaluate the effect of chemical disinfectants on surface hardness of the acrylic resins. Material and Methods: Forty specimens (65 mm in length, 10 mm in width and 2.5 mm thick) were manufactured from heat cured acrylic resins for hardness testing according to ISO 1567:1999. The study consisted of four main sets according to the disinfectants applied (control, 1% hypochlorite, 4 % chlorhexidine, and Efferdent®) and each set contained ten specimens. All specimens were placed in saline solution at 37°C and incubated for 60 days. Acrylic specimens were then tested by using a hardness tester three times and the average reading was recorded. All data were analyzed using SPSS version 16. The results were analyzed at a significant level (p≤0.05). The ANOVA (analysis of variance) test was used to assess whether there were any significant differences among all groups. The comparisons between means were obtained by using a Tukey test. Results: There was a slight decrease in the mean values of surface hardness after immersing in chemical disinfectants. The chlorhexidine-assigned specimens had the lowest value of mean surface hardness. On the other hand, the control group had the highest mean value. However, there were no significant differences regarding surface hardness among all groups (p>0.05). Conclusion: The use of chemical disinfectants slightly decreases the surface hardness of heat-cured acrylic resins.